The Reagan moment : America and the world in the 1980s - Hunt, Jonathan R., 1983-; Miles, Simon, 1988- (Cornell University Press, 2021)
"A worldwide collection of histories of US foreign relations during the two presidential administrations of Ronald Reagan"--